PENGARUH KEGIATAN MENGHIAS BONEKA PENGANTIN BATAK TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK NAFIRI KASIH KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Rismelda Rismelda; Zulkifli Zulkifli; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims 1) To determine the fine motor skill of children aged 4-5 years in TK Nafiri Kasih District Tapung Hulu regency Kampar before the application of decorating dolls activities. 2) To determine the fine motor skill of children aged 4-5 years in TK Nafiri Kasih District Tapung Hulu regency Kampar after the application of decorating dolls activities. 3) To determine how much influence the application of decorating dolls activities against the fine motor skills of children aged 4-5 years in TK Nafiri Kasih District Tapung Hulu regency Kampar. This type of research is an experimental research. The research sample is the children class A consisting of 15 people, 8 girls and 7 boys. Colleting data using observation and documentation. Based on the survey result relevaled that 1) Fine motor ability of children aged 4-5 years in TK Nafiri Kasih District Tapung Hulu regency kampar before treatment is given in the from of decorating dolls activities is low. 2) The ability to fine motor skills of children aged 4-5 years in TK Nafiri Kasih District Tapung Hulu regency kampar after treatment is given in the from of decorating dolls activities has increased and is high. 3) The decorating dolls activities has a significant influence in the from of an increase on the fine motor skills of children before and after treatment. 4) activity decorating dolls has the effect of 38,69% against an increase in the fine motor skills of children aged 4-5 years in kingdegarten Nafiri Kasih District Tapung Hulu regency Kampar.Key words: Decorating Dolls, Fine Motor